Phase transformation under isostatic pressure in HIP. (27th May 2017) - Angré, Alexander; Ahlfors, Magnus; Chasoglou, Dimitris; Larsson, Linn; Claesson, Erik; Karlsson, Oskar
ABSTRACT: The new HIP cooling systems enable very fast cooling rates under isostatic pressure. This does not only enable shorter HIP cycles but also allows complete heat treatment cycles to be performed in one HIP cycle. It has been shown in previous studies that extreme pressures of several thousand bar can push phase transformation towards longer times. The new URQ HIP cooling systems give the opportunity to investigate the impact of pressures up to 2000 bar on phase transformation time dependency. For each of the two materials in this study, a comparison of austenite phase transformation time at 100 and 1700 bar was performed. The study was performed by isothermal heat treatment of specimens for a specific time followed by quenching. To evaluate the influence of pressure on hardenability, the phase fractions were evaluated using grid method on SEM images. The study found significant influence of HIP pressure on hardenability.